Adhesion of Dust Particles to Common Indoor Surfaces in an Air-Conditioned Environment - Tan, Cher Lin Clara; Gao, Shaokai; Wee, Boon Siong; Akua, Asa-Awuku; Beng Joo, Reginald Thio (Taylor & Francis Group, 2014)
Adhesion between dust particles and indoor surfaces can lead to negative effects on human health by triggering allergic and asthmatic reactions. In this study, adhesion forces of indoor office dust and activated carbon (AC, as model soot) particles to four common indoor materials (Al, Cu, PVC, and glass) were measured by colloidal probe atomic force microscopy. Chemical analysis of office dust shows it is largely made up of oxygenated hydrophilic organic carbon material. Both metal surfaces experienced weaker dust and AC adhesion than PVC or glass by up to 2–12 times lower primarily due to the presence of attractive electrostatic forces in the latter two (non-conducting) surfaces. Dust and AC adhesion were also highly sensitive to surface roughness, with an inverse relationship between adhesion force and roughness due to the reduction in contact area between the particle and a rougher material surface. Capillary forces play only a minor or negligible role in dust and AC surface adhesion. Adhesion models utilizing a purely van der Waals approach such as the simple Hamaker model and modified Rumpf’s model are insufficient to determine the actual particlesurface contact radii and requires the accounting of non-van der Waals forces to adhesion.